Komunitas fitoplankton di perairan Danau Laut Tawar Kabupaten Aceh Tengah, Provinsi Aceh - Nurfadillah N; Ario Damar; Enan M. Adiwilaga (Depik, 2012)
Abstract. The aims of the present study was to evaluate community structure and biomass of phytoplankton based on the depth stratification in the waters of Lake Laut Tawar. Sampling was conducted during March and April 2010. The results showed that 43 species of phytoplankton belonging to five classes were found in Lake Laut tawar. The most common class was Chlorophyceae with 20 genera, followed by Bacillariophyceae (diatoms) by 9 genera, Cyanophyceae (10 genera), Dinophyceae (2 genera), and Euglenophyceae (2 genera). The highest species composition was found at II with 15 m depth (24 genera), while the highest abundance of phytoplankton was occured at station with 10 depth (155600 cells/l), while the lowest abundance was obtained at 15 depth (12745 cells/l). Overall the phytoplankton population in Lake Laut Tawar was dominated by Bacillarophyceae. In addition, the diversity index of phytoplankton was in moderate level (2.34), while the evenness index was ranged from 0.43 to 0.87, indicate the distribution of the individuals of each species was varied, however there was no predominant species detected.Keywords. Phytoplankton, structure community, Laut Tawar Lake.